RACE DISCRIMINATION IN TONY KUSHNER’S MOVIE SCRIPT LINCOLN - Sri Astuti Rambe; Asnani - Asnani (Universitas Islam Sumatera Utara, 2021)
This research is concerned with the race discrimination in Tony Kushner’s movie script Lincoln. A story of four months of struggle of Lincoln and the Republican party and its supporters to pass the 13th amendment which formally abolished slavery in the United States passing the Senate on April 8, 1864, and the House on January 31, 1865 and approved by President Abraham Lincoln on February 1, 1865. The analysis focuses on the types of race discrimination: the direct and the indirect of race discrimination and the negative impacts of race discrimination adopted from Liliweri. This research used descriptive qualitative research. The one adopted in the research is proposed by Khotari and Bogdan Taylor. The finding shows that the direct race discrimination is an act of limiting a job based on race. It comes from black soldiers. There is also a tendency to discriminate between groups and beliefs with human law itself. The negative impacts of race discrimination are slavery and civil war. Furthermore, race discrimination also causes heavy casualties between whites and blacks by taking over place the territories of the minority.